Kajian Hukum Terhadap Proses Pemberhentian dan Pengangkatan Perangkat Desa di Kawasan Sumba Barat Daya: Legal Study on the Termination and Appointment Processes of Village Officials in the Southwest Sumba Region - Liany Angsana Dewi Hadi; Eko Primananda (Faculty of Law, Universitas Trisakti, 2024)
The decisions of the State Administrative Court play a crucial role in upholding the law and ensuring justice. The implementation of these decisions is also a critical part of ensuring justice. Efforts to ensure the execution of decisions, such as coercive measures and administrative sanctions, need to be taken to ensure that court decisions are truly enforced. This way, the principle of justice can be more effectively realized at all stages of the legal process, from hearings to the implementation of decisions. The research questions in this study are: (1) Whether the dismissal and appointment of village officials in Weepangali Village comply with Law Number 6 of 2014 concerning Villages; (2) How is the implementation of the procedures for the dismissal and appointment of village officials in Weepangali Village after Decision Number 39/G/2022/PTUN? The research found that the process of appointing the new Village Apparatus was carried out by dismissing the old Village Apparatus without any prior notification letter and without any clear reason. The conclusion is that the process of appointing and dismissing Village Apparatus is not in accordance with statutory provisions.